Incidência da escápula alada e morbidade dos membros superiores de pacientes no pós-operatório do tratamento do câncer de mama com abordagem axilar - Rizzi, Samantha Karlla Lopes de Almeida [UNIFESP] (2015)
The incidence of winged scapula was 8.03% after 15 days of surgery breast cancer with axillary approach. After six months postoperatively the prevalence dropped to 3.27%. 2) The scapular winging was associated with higher frequency of lymphadenectomy Axillary (22.58%) compared to the sentinel lymph node biopsy (2.86%). There was no significant difference in the incidence of different types of breast surgery. 3) dyskinesia scapula increased, mainly from three months surgery. 4) The presence of scapular asymmetry did not change over six months postoperative, or had no relation to the appearance of winged scapula or increased dyskinesia scapula after surgery. 5) There was a decrease in the amplitude of flexion, adduction, abduction and shoulder external rotation postoperative recovery and amplitude average of all movements during the six months post-surgery. 6) The increased pain after surgery, but remained low throughout the follow-up and six months after surgery showed no difference when compared to the preoperative phase. 7) The scapular winging was associated with greater morbidity for shoulder the movements of flexion, abduction and adduction, no difference to ache.